Collaborative Participation Strategy to Improve the Quality of Music Ministry in the Church - Rupiyono, Leo Agung (Jurnal Seni Musik, 2025)
The music ministry in church worship is a crucial element that supports the solemnity and spiritual depth of the congregation. This study aims to examine the implementation of a collaborative participation strategy to improve the quality of church music ministry. Employing a qualitative method with a case study design at GKJ Salatiga Selatan, data were collected through participatory observation, in-depth interviews, and document analysis. The findings reveal that the collaborative participation strategy, which includes ongoing training, reflective evaluation, and open communication forums, significantly enhances the technical and spiritual quality of the church's music service. Active involvement of all ministry members produces cooperation that strengthens team cohesion and fosters a shared ownership of the ministry. Consequently, this strategy can be regarded as a practical and contextual framework for developing music ministry within the church.